The Surgeon’s Proficiency Affected Survival Outcomes of Minimally Invasive Surgery for Early-Stage Cervical Cancer: A Retrospective Study of 851 Patients - Yang, Ying; Huang, Yue; Li, Zhengyu (Frontiers in Oncology, 2021)
Purpose To compare the clinical outcomes of patients with early-stage cervical cancer who underwent minimally invasive surgery (MIS) by surgeons in different phases and evaluate whether the proficiency of surgeons affects the survival outcomes. Materials and Methods A total of 851 patients with early-stage cervical cancer who underwent radical hysterectomy between January 2008 and June 2018 (every year from January to June) at a tertiary hospital were retrospectively analyzed. We categorized patients into four phases according to their sequence (phase one, 1-10 cases; phase two: 11-20 cases; phase three: 21-30 cases; phase four: > 30 cases). Demographics and clinical and pathological data were collected and analyzed. Results There were no statistical differences between the open surgery and MIS groups regarding three- and five-year overall survival (OS) and disease-free survival (DFS). The OS and DFS of patients in the MIS group in phase one were significantly lower than those in later phases and those in the open surgery group after adjustment (OS, P = 0.009; HR, 2.896; 95%CI, 1.303-6.435; DFS, P = 0.009; HR, 2.712; 95%CI, 1.289-5.706). Survival outcomes were not statistically significant when comparing different surgeons. Conclusion The phase one cases of MIS had lower OS and DFS than those in later phases and those in the open surgery group. Thus, we suggest that the proficiency of surgeons is associated with survival outcomes of MIS. Favorable outcomes can be obtained after a certain number of MIS cases.